Exploring the Role of Physical Activity-Induced Dopamine and Serotonin Release in Enhancing EFL Learners' Confidence in Speaking English - Ahmad Rifai (Foreign Language Instruction Probe, 2025)
Many Indonesian EFL learners experience difficulties in speaking English confidently due to anxiety, fear of making mistakes, and reluctance to speak in front of others. This study explored EFL learners' confidence in speaking English through physical activity-induced dopamine and serotonin release. A qualitative case study was conducted at SMP Negeri 1 Krangkeng, Indramayu, West Java, involving classroom observations and semi-structured interviews with six eighth-grade students representing different levels of speaking confidence and one English teacher. Data were analyzed using Creswell's (2017) qualitative procedures and Braun and Clarke's (2021) thematic analysis. The findings showed that light and enjoyable physical activities, such as stretching, ice-breaking, games, and movement-based speaking tasks, helped students feel more relaxed, motivated, and confident in speaking English. These activities reduced nervousness, fostered a supportive classroom atmosphere, and improved students' emotional and linguistic readiness for speaking. The study concludes that integrating interactive physical activities into EFL speaking instruction can effectively enhance learners' confidence and participation in English speaking.